2021
DOI: 10.3389/fpubh.2021.578917
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Experiences of Receiving Professional Support Through Extended Home Visits During Pregnancy and Early Childhood—A Phenomenographic Study

Abstract: Background: While becoming a parent can be challenging for all, it can particularly be challenging for those parents and children who are in a vulnerable situation—e.g., in families whose members have problems related to health, relationships, or socioeconomic status. It is essential for health care professionals to identify the more vulnerable families at an early stage. Home visits are one cost-effective way of identifying and supporting such families. This study describes the parental experiences of an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Extended home visits also foster social support through social activities at child health centres as well as promote integration into, e.g. Swedish society for migrant parents (Bäckström et al., 2021). Previous research has reported that home visits provide early, individual and family‐centred support (Rautio, 2013), which strengthens both the self‐confidence and social networks of parents (Minkovitz et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Extended home visits also foster social support through social activities at child health centres as well as promote integration into, e.g. Swedish society for migrant parents (Bäckström et al., 2021). Previous research has reported that home visits provide early, individual and family‐centred support (Rautio, 2013), which strengthens both the self‐confidence and social networks of parents (Minkovitz et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The researchers conducted the recruitment between autumn 2019 and winter 2020 using convenience sampling. The recruited participants were also part of another research project, Reinforced Parenting-Extended Home Visits (38). Child healthcare (CHC) nurses asked parents who met the inclusion criteria of their interest to participate.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…The support provided them reduces stress and anxiety, increasing their quality-of-life assessment. It has a positive effect on psychophysical well-being, reducing the anxiety associated with hospitalization [ 27 , 28 , 29 ]. According to reports by other authors, the support of medical staff was not able to compensate for the lack of a loved one.…”
Section: Discussionmentioning
confidence: 99%